2013
DOI: 10.1016/j.jprot.2013.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Global proteomic analysis in trypanosomes reveals unique proteins and conserved cellular processes impacted by arginine methylation

Abstract: Arginine methylation is a common posttranslational modification with reported functions in transcription, RNA processing and translation, and DNA repair. Trypanosomes encode five protein arginine methyltransferases, suggesting that arginine methylation exerts widespread impacts on the biology of these organisms. Here, we performed a global proteomic analysis of T. brucei to identify arginine methylated proteins and their sites of modification. Using an approach entailing two-dimensional chromatographic separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
98
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(104 citation statements)
references
References 81 publications
6
98
0
Order By: Relevance
“…Such as we have shown that the modification is involved in the regulation of subcellular localization or shuttling of SERBP1 [26]. From a proteomic study in trypanosomes, a subset of arginine methylated protein are involved in intracellular trafficking [31], suggesting that the cellular methylation conditions might regulate the protein transport machinery in some way. We detected predominant nuclear distributions of the endogenous or transfected CNBP proteins whether HeLa cells were under normal methylation or hypomethylation conditions.…”
Section: Discussionmentioning
confidence: 90%
“…Such as we have shown that the modification is involved in the regulation of subcellular localization or shuttling of SERBP1 [26]. From a proteomic study in trypanosomes, a subset of arginine methylated protein are involved in intracellular trafficking [31], suggesting that the cellular methylation conditions might regulate the protein transport machinery in some way. We detected predominant nuclear distributions of the endogenous or transfected CNBP proteins whether HeLa cells were under normal methylation or hypomethylation conditions.…”
Section: Discussionmentioning
confidence: 90%
“…together with manual data curation or with orthogonal methylpeptide validation), remains a highly popular method of filtering methyl-PSMs (see Table I). When applied as a standalone technique, the most common application of the approach involves obtaining methyl-PSM thresholding criteria based on global FDR estimates (4,5,8,9); two recent studies have, however, made use of separate methyl-PSM FDR esti-…”
Section: Discussionmentioning
confidence: 99%
“…Despite the prospective issues associated with sequence database search-derived methylpeptide identifications, the use of orthogonal methylpeptide validation in large scale methylation site discovery studies remains sporadic. Although several such studies have employed heavy-methyl SILAC (6,7,14,16) or other closely related methylpeptide-specific labeling techniques (12,13) to validate methylation sites, others have chosen to bypass orthogonal validation and to instead predominantly rely on the target-decoy approach to provide estimates for high stringency methylpeptide filtering criteria (4,5,8,9,15) or to inform manual data curation (see Table I) (10,11). This irregular use of orthogonal methylpeptide validation is a reflection of the fact that in-depth studies into methylpeptide FDRs have yet to be performed.…”
mentioning
confidence: 99%
“…Posttranslational modification of proteins is one such mechanism that allows rapid responses to internal and external cues (8). Our proteome-wide studies revealed that about 15% of the proteome of T. brucei insect vector procyclic forms (PFs) 2 harbors arginine methyl marks (9,10). 3 Thus, arginine methylation is poised to play a crucial role in regulating T. brucei biology.…”
mentioning
confidence: 99%